Trends in research using plant genetic resources from germplasm collections: from 1996 to 2006 - Dulloo, Mohammad Ehsan; Thormann, I.; Fiorino, E.; Felice, S. de; Rao, V.R.; Snook, Laura K. (Wiley, 2013)
This paper examines how the use of genebank materials has changed from 1996 to 2006 using a similar survey by Dudnik et al. (2001) of reports published in 1996 as a baseline. Articles published in four journals generally used by genetic resource scientists were analyzed in each 2006 issue, as was done by Dudnik et al. in 2001. Studies involving genebank materials were selected and the following data were recorded: species used, locations of studies, affiliation of researchers, and sources of the materials and their uses. The analysis identified 320 studies in which a total of 57,935 accessions from 148 genebanks were used. Crop wild relatives were targeted in 20% of the studies. The study showed that a much higher percentage of accessions came from developed (87%) than from developing countries (7%) while 6% were supplied by CGIAR centers. The results in 2006 revealed an increase in the proportion of studies using genebank materials as compared to 1996. Genebank materials were used primarily for studies of genetic diversity, agromorphological and nutritional quality characteristics, biotic resistance, and mapping. Of the institutions carrying out the studies, 93% were from the public sector. However, there are still some barriers that limit the exchange of germplasm across borders. This implies that greater awareness among policymakers will be needed to facilitate the necessary exchange of plant genetic resources between countries to improve agricultural production.